2002
DOI: 10.1002/dvdy.10148
|View full text |Cite
|
Sign up to set email alerts
|

Precocious expression of cardiac troponin T in early chick embryos is independent of bone morphogenetic protein signaling

Abstract: Cardiac troponin T (cTNT) is a component of the troponin complex, which confers calcium sensitivity to contraction in skeletal and cardiac muscle. Although it is thought that most components of the contractile myofibril are expressed exclusively in differentiated muscle cells, we observed that mRNAs coding for cTNT were detectable in explanted late gastrula mesoderm at least 12 hr before cardiac myocyte differentiation. We therefore conducted a detailed analysis of cTNT gene expression in the early chick embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 52 publications
(63 reference statements)
2
18
0
Order By: Relevance
“…These findings point to a role of NOG just after mesoderm formation and before cardiomyocyte differentiation. Ectopic delivery of BMP2 medial to the heart-forming regions results in an expansion of the expression domain of NKX2-5, TBX2, GATA4, GATA5, GATA6 and SMAD6, but not of TBX5, SMAD1, SMAD5, HAS2 and TNNT2 (cardiac Troponin T), whereas lateral delivery does not affect the expression domains of these genes [19,27,28,[36][37][38]. In both the promoter of NKX2-5 and SMAD6 a binding site for SMAD was identified [39,40].…”
Section: Formation Of Cardiomyocytes In Heart-forming Regionsmentioning
confidence: 95%
“…These findings point to a role of NOG just after mesoderm formation and before cardiomyocyte differentiation. Ectopic delivery of BMP2 medial to the heart-forming regions results in an expansion of the expression domain of NKX2-5, TBX2, GATA4, GATA5, GATA6 and SMAD6, but not of TBX5, SMAD1, SMAD5, HAS2 and TNNT2 (cardiac Troponin T), whereas lateral delivery does not affect the expression domains of these genes [19,27,28,[36][37][38]. In both the promoter of NKX2-5 and SMAD6 a binding site for SMAD was identified [39,40].…”
Section: Formation Of Cardiomyocytes In Heart-forming Regionsmentioning
confidence: 95%
“…However, the expression of smooth muscle a-actin (SMA), which is first expressed in the precardiac mesoderm and recruited into the nascent myofibrils as an initial a-actin, is not regulated by endoderm or BMP (Nakajima et al 2002). Other experiments have shown that cardiac troponin T (cTNT), Tbx3, and Tbx5 are also expressed in the anterior lateral plate mesoderm and that their expression is not endoderm-dependent (Schlange et al 2000;Yamada et al 2000;Antin et al 2002). These observations suggest that (1) endoderm-emitted BMP together with FGF regulates heart specification as well as terminal differentiation and that (2) in addition to endoderm-derived signaling, an additional regulatory pathway(s) appears to exist for the activation of cardiac genes ( Fig.…”
Section: Signaling Regulates Heart Specification and Differentiation mentioning
confidence: 96%
“…Explantation experiments using chick blastoderm explants showed that signaling from the hypoblast is required to induce cardiac myogenesis in the early epiblast and that the hypoblast-derived signal(s) appears to act upstream of the heart-inducing signals emitted from the anterior lateral endoderm (Yatskievych et al 1997). Several genes expressed in the anterior lateral mesoderm, such as those for SMA, cTNT, and Tbx5, are regulated independently of endoderm-emitted signaling, including BMP (Schlange et al 2000;Yamada et al 2000;Antin et al 2002;Nakajima et al 2002). Genetic studies in the mouse and zebrafish have shown that transforming growth factor beta (TGFb) signals of the Nodal family are essential for the formation of mesoderm in vertebrates (Schier and Shen 2000).…”
Section: Signaling Regulating Heart Mesoderm Formation At the Blastulmentioning
confidence: 99%
“…GATA-4 is an important transcription factor in early myocardial development. cTnT is a protein whose only known function is as part of the troponin complex of myofibrils in cardiac and embryonic skeletal muscles (Antin et al 2002). Alpha-actin is one of the isoforms of the actin family found in muscle tissue (Oma and Harata 2011).…”
Section: Cultured Afs Cells (Both C-kitmentioning
confidence: 99%